From the information given,
f(x) = 4x + 7
g(x) = 3x - 5
The first step is to find F • g(x)
To do this, we would substitute x = 3x - 5 into f(x) = 4x + 7. It becomes
F • g(x) = 4(3x - 5) + 7
We would apply the distributive property of multiplication by mutiplying each term inside the parentheses by the term outside. It becomes
F • g(x) = 4 * 3x + 4 *- 5 + 7
F • g(x) = 12x - 20 + 7
F • g(x) = 12x - 13
We would find F • g(-4) by substituting x = - 4 into F • g(x) = 12x - 13. It becomes
F • g(- 4) = 12(- 4) - 13 = - 48 - 13
F • g(- 4) = - 61